PENDAMPINGAN INVENTARISASI DAN PENGHAPUSAN SARPRAS UNTUK TERTIB ADMINISTRASI SMP YPK HEDAM DAN SD YPK SION PADANG BULAN JAYAPURA - Aryesam, Agnes; Sampe, Novihta; Toam, Agnes; Maseyra, Mutiara; Tanggronefa, Delvi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT The inventory and disposal of school facilities and infrastructure (sarpras) constitute a critical component of effective and accountable school asset management. However, field observations reveal that many schools—including SMP YPK Hedam and SD YPK Sion Padang Bulan in Jayapura City—have yet to implement these processes in a systematic and compliant manner. Key challenges include the absence of valid inventory data, non-compliance with proper disposal procedures, and limited administrative competence among school personnel. This community service initiative aims to provide both technical and educational support to schools through structured training, simulations, and hands-on practice. The implementation methods include preliminary observations, the development of training materials, demonstrations of inventory and disposal procedures, and participatory evaluations. A participatory approach was employed, involving principals, teachers, and administrative staff in each stage of the program. The results indicate a significant improvement in participants' understanding and skills related to asset recording, the preparation of official disposal reports, and the classification of asset conditions. Furthermore, the activity fostered a collective awareness of the importance of administrative order in managing school infrastructure and resources. In conclusion, the practice-based assistance effectively strengthened schools' managerial capacities, enhanced asset accountability, and laid the groundwork for a more professional and transparent educational administrative system. ABSTRAK Inventarisasi dan penghapusan sarana-prasarana (sarpras) merupakan bagian penting dari pengelolaan aset sekolah yang efektif dan akuntabel. Namun, praktik di lapangan menunjukkan bahwa banyak sekolah, termasuk SMP YPK Hedam dan SD YPK Sion Padang Bulan di Kota Jayapura, belum melaksanakan kedua proses tersebut secara tertib. Permasalahan yang dihadapi mencakup ketiadaan data inventaris yang valid, prosedur penghapusan yang tidak sesuai aturan, serta rendahnya pemahaman administrasi oleh tenaga kependidikan. Kegiatan pengabdian ini bertujuan untuk memberikan pendampingan teknis dan edukatif kepada pihak sekolah melalui pelatihan, simulasi, dan praktik langsung. Metode pelaksanaan mencakup observasi awal, penyusunan materi pelatihan, demonstrasi prosedur inventarisasi dan penghapusan, serta evaluasi partisipatif. Pendekatan dilakukan secara partisipatif dengan melibatkan kepala sekolah, guru, dan staf administrasi dalam setiap tahapan kegiatan. Hasil kegiatan menunjukkan peningkatan signifikan dalam pemahaman dan keterampilan peserta mengenai pencatatan aset, penyusunan dokumen berita acara penghapusan, serta klasifikasi kondisi barang. Selain itu, terbentuk kesadaran kolektif akan pentingnya tertib administrasi dalam pengelolaan sarpras. Simpulan dari kegiatan ini menegaskan bahwa pendampingan berbasis praktik mampu memperkuat kapasitas manajerial sekolah, meningkatkan akuntabilitas aset, dan menjadi langkah awal menuju sistem administrasi pendidikan yang profesional dan transparan.